Pengaruh Country Of Origin Dan Brand Image Terhadap Minat Beli Skincare Innisfree : Studi pada Remaja Perempuan di Kabupaten Parigi Moutong, Sulawesih Tengah - era agustina yamini; Nisa Andriani; Tzulkarnain (At-Thariqah: Jurnal Ekonomi, 2024)
Country of origin and brand image are two important requirements to influence customers’ buying interest. The demand for Indonesian on skincare products is very high. Because of the high demand and interest in beauty products, many Korean beauty products get in Indonesia. One of them is Innisfree. The research aimed to know the influence of Country of Origin toward buying interest of Innisfree skincare, the influence of brand image toward buying interest of Innisfree skincare, the influence of both Country of Origin and brand image toward the buying interest of Innisfree skincare. The research method used survey research. The population was woman teenagers who had or being used the Innisfree skincare products from South Korea. The sampling method applied purposive sampling based on 50 respondents. The data collection used an effectiveness questionnaire test (validity) and reliability. The influence between the country of origin and the brand image can be illustrated in 44,4% variables of buying interest, while 55,6% variables can be explained by other variables that are not available in this research.